Pengembangan E-Modul Mata Kuliah Psikologi Pendidikan untuk Mahasiswa Jurusan Pendidikan Guru PAUD UNM - Fitriani Dzulfadhilah; Rusmayadi; Sitti Nurhidayah Ilyas; Sri Rika Amriani H; Nurul Fadhillah S (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This community service activity is to develop E-Modules for Educational Psychology courses targeting students of the Early Childhood Education Teacher Education Department, Faculty of Education, Makassar State University as participants. There are 105 PGPAUD FIP UNM batch 2021 students who are divided into three classes as participants in the E-Module practical test activities. The purpose of this service activity is to develop innovative and creative teaching materials using case method and Project Based Learning models. This service is carried out by first making a module using the Canva application, then converting it into an E-Module using the flip book application. The preparation of E-Modules is carried out through several activities, such as compiling lecture materials, conducting Forum Group Discussions (FGDs) with lecturers and kindergarten teachers. After completion, the E-Module is socialized to students so that it can be accessed effectively on the website of the PGPAUD Department FIP UNM Then the practicality test of the E-Module was carried out on 105 PGPAUD FIP UNM Batch 2021 students. The results of the E-Module practicality trial showed that in the aspect of the Physical form or E-Module Design with a percentage of 72% of students who rated very good, 26% rated good. In the aspect of E-Module material/content, 81% of students rated it very good, 19% of students rated it good. In the aspect of being economically accessible, 76% of students rated it very good, 23% rated it good, 1% was not good. In the aspect of ease of access related to usage time, 61% of students rated very good, and 35% of students rated good, 3% rated not good, and 1% rated very bad. The results of this service are making students have teaching materials in the form of E-Modules that are innovative, attractive and very accessible.